Evaluation of hepatotoxic and nephrotoxic effects after 2 weeks treatment of piroxicam sulfonated derivatives in albino rats - Shaheen, Ghazala; Habib, Syed Hamid; Khizar, Syeda Huma; Safiullah, Safiullah; Malik, Muhammad Omar; Khan, Naeem; Tariq, Shafique Ahmad (Pakistan Journal of Physiology, 2019)
New pharmacotherapy with good efficacy and less side effects is required for management of pain. Use of Piroxicam is associated with side effects. Sulfonated piroxicam derivatives (SPD) have been introduced to minimized adverse effects associated with its use. We aim to find hepatotoxic and nephrotoxic effects of SPD in Albino rats after 14 days of treatment.This was an experimental study carried out at the Institute of Basic Medical Sciences, Khyber Medical University Peshawar. Healthy 24 albino rats were divided into 5 groups. One control group and four experimental groups having two compounds (compound I and II) in a dose of 10mg/kg and 20mg/kg respectively were administered for 14 days. Blood was obtained for liver and renal function tests . Histology of liver and kidney were performed after sacrificing rats. Data was analyzed with SPSS using one way ANOVA with post hoc analysis. Among the LFTs alkaline phosphatase values were significantly high for compound II when used in the 20mg/kg concentration than control . The Alanine aminotransferase and aspartate aminotransferase concentrations were not significantly different between the groups . There was significant difference in blood urea among the groups and in post hoc comparison the main difference was observed in the compound II in higher concentrations . The mean final score observed for liver injury and kidney injury (2.5-3) suggesting there was less pronounced effect on both liver and kidney respectively. The Piroxicam sulfonated derivatives show minimal and reversible toxic effects on liver and kidney after 2 weeks treatment.